Creating of Spiritual Leadership Program for Leaders in a Healthcare Organization - Chongvisal, Rattigorn (Journal of Behavioral Science for Development, 2024)
This study design applied the quasi - experimental research with randomized pretest-posttest control group design and primarily aims to develop a spiritual leadership program as well as to develop and validate a handbook on training spiritual leadership for leaders in a healthcare organizations. The study participants consisted of 62 leaders in a healthcare organizations (i.e., executives, managers, and those who were prepare to be promoted to manager or executive). The participants were divided into two groups, 32 participants were in the experimental group and 30 were in the control group by simple random sampling. Both quantitative and qualitative data collection were performed. Results: 1) the program and handbook on training spiritual leadership for leaders in organizations were obtained. This program consisted of four modules: module 1 connectedness to self and one’s own spirituality, module 2 connectedness to others and society, module 3 development of spiritual leadership, and module 4 follow-up after spiritual leadership training. 2) For the try-out to validate the effectiveness of training program, results revealed that spiritual leadership of the leaders attending the spiritual leadership program was significantly higher than those who did not attend the program (p < .05). In addition, results of the qualitative data revealed that the leaders who attended the program had greater knowledge and understanding about spiritual leadership. Also, their spiritual leadership had increased, connectedness to self, others, and society had developed.